2015
DOI: 10.1111/jai.12843
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of six fish species from the Zengqu River and the Ouqu River, southwest China

Abstract: This study provides the first report of length-weight relationships (LWRs) for six endemic fish species collected from the Zengqu River and the Ouqu River, two of the tributaries to the upper reaches of the Jinsha River, southwest China. Samples were obtained in May 2013 and September 2013 using various types of fishing gear. A total of 413 specimens belonging to six fish species were analyzed; their LWRs were W = 0.0069L 3.086 (r 2 = 0.987) for Schizothorax wangchiachii (Fang, 1936), W = 0.0076L 3.029 (r 2 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
1
12
2
Order By: Relevance
“…For a comparison of b values calculated in our study with 95% confidence limits of Bayesian estimation reported in FishBase (Froese & Pauly, ), the fish species were divided into two groups: (a) one specie with b values within the Bayesian's confidence intervals ( T. siluroides ); (b) three species with both values of the intervals ( S. anteroventris , S. lissolabiatus and T. markehenensis ). Differences in the LWR can be attributed to several factors: a number of factors such as environmental (seasonal variation, habitat type, geographic region) and biological (population, gonadal maturity, sex, growth phase, diet, degree of stomach fullness, health and general fish condition) (Xia, Chen, & Xiong, ; Zhang, Wang, & Liu, ; Zhu, Yang, Liu, & Li, ); however, these factors were not considered in the present study. In addition, the narrow sample size and/or the length range of T. markehenensis possibly affected the b values in the study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For a comparison of b values calculated in our study with 95% confidence limits of Bayesian estimation reported in FishBase (Froese & Pauly, ), the fish species were divided into two groups: (a) one specie with b values within the Bayesian's confidence intervals ( T. siluroides ); (b) three species with both values of the intervals ( S. anteroventris , S. lissolabiatus and T. markehenensis ). Differences in the LWR can be attributed to several factors: a number of factors such as environmental (seasonal variation, habitat type, geographic region) and biological (population, gonadal maturity, sex, growth phase, diet, degree of stomach fullness, health and general fish condition) (Xia, Chen, & Xiong, ; Zhang, Wang, & Liu, ; Zhu, Yang, Liu, & Li, ); however, these factors were not considered in the present study. In addition, the narrow sample size and/or the length range of T. markehenensis possibly affected the b values in the study.…”
Section: Discussionmentioning
confidence: 95%
“…For a comparison of b values calculated in our study with 95% confidence limits of Bayesian estimation reported in FishBase (Froese & Pauly, 2017), the fish species were : coefficient of correlation. Xiong, 2016;Zhang, Wang, & Liu, 2017;Zhu, Yang, Liu, & Li, 2015); however, these factors were not considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The b value (2.986) in G. maculatum estimated by the present study is lower than b values (female = 3.142, male = 3.147) of G. maculatum from the Nianchu, Lhasa and Nyang Rivers (Li & Xie, ). Differences in the LWR can be attributed to several factors such as area, gonad maturity, diet, stomach fullness, health, age, fishing time (seasonal and annual fluctuations; Zhu, Yang, Liu, & Li, ). Among them, one more important reason attributed to the LTR estimates vary is methodology effects (net selectivity).…”
Section: Discussionmentioning
confidence: 99%
“…These rivers have highly endemic fishes, which is not well investigated. Length‐weight relationships (LWRs) are important in field studies that are limited by resources and time (Xiong et al., ; Zhu, Yang, Liu, & Li, ), essential to estimate growth rates, length and age structures, and other components of fish population dynamics (Kolher, Casey, & Turner, ), and useful for monitoring the state of health of a population (Cone, ). The aim of this study was to analyse length‐weight relations for the species living in the Dogxung Zangbo River and the upper reaches of the Yarlung Tsangpo River.…”
Section: Introductionmentioning
confidence: 99%